Measures of Quality of Life in People with Aphasia. A systematic review - Garrido del Águila, Dunia; Niño, Ana Lydia; Carballo, Gloria (Revista de Investigación en Logopedia, 2022)
Aphasia after stroke and its different negative conditions derived, affect the quality of life (QoL) of the person. The aim of this study is to describe and analyze the literature of last five years in order to identify and quantify relevant aspects related to QoL and its assessment in people with aphasia (PWA). For that goal, three databases were consulted (PsycINFO, Medline, and Psicodoc). Thirty-eight studies were included. The characteristics of the studies were coded and analyzed, and the quality of these studies were evaluated following guidelines established by STROBE and the NIH. The results show that the most frequently used QoL assessment test was the Stroke and Aphasia Quality of Life Scale-39 (SAQOL-39) (n= 19, 50.00%). In most studies, regardless of the assessment tests, PWAs have a low QoL. The selected studies present a medium-high level of methodological quality. As a conclusion it can be said that in addition to the limiting aspects of communication and language, aphasia negatively affects the overall QoL of the patient. The development of QoL assessment tests can help professionals to plan an appropriate intervention.